Le patient : le tiers impensé dans l'apprentissage du raisonnement clinique - Delphine Guyet; Jean-Luc Rinaudo
As part of the "reengineering" of initial studies of physiotherapy, it is sought to understand the situation of transmission-learning of the clinical reasoning of a student and his tutor in an internship situation, during the first patient encounter. The first session is considered a problematic situation in the link professions. Using Houssaye's pedagogical triangle (2014) and Lescouarch's quadrangle (2018), the interactions of guardianship and shoring are looked at. The approach used is part of the field of professional knowledge. The student performs, under supervision, a first care session with a patient accustomed to this liberal practice. The survey methodology implemented includes recordings of care sessions. The comments are based on the analysis of data from five patient/tutor/student triads. The analysis of the interactions and the different positions taken by the actors during the session allows modeling in an educational pyramid, placing the patient as a third part mediator in the learning of clinical reasoning. He assumes several roles depending on the support and the pedagogical posture he adopts. The patient's role in this learning be an unthought of the training.